Dispute on Security Framework Model of MFCC Mixed Methods in Speech Recognition System - Pratiwi, Heni Ispur; Kartowisastro, Iman Herwidiana; Soewito, Benfano; Budiharto, Widodo (Bright Publisher, 2025)
An audio recording system device has unprecedented activities of its authorized users which in a particular way cause vulnerability to the system. It starts to get into a fuzzy condition and deteriorate the system sensitivity in detecting unauthorized access to pass through, then the system inclination may occur. One case is when separate users picked speech voices with similar keywords to set their usernames or password. Moreover, when users are siblings or twins that could have merely similar voices. Troublesome of this situation leads to a less sensitive manner of a security system, and in some situations, the system could operate blocking authorized users themselves to get access. This paper defines a proposed method to resolve the situation by combining Mel Frequency Cepstral Coefficient with other methodologies, which have been implemented for many other research’ specific objectives as well. This paper displays to prove its combination with an interval scoring in Fuzzy Relation complements a resolution to tackle the security of fuzzy issues mentioned. The Mel Scale has its capacity of delivering extractions output from audio input data, it is called as spectral centroids which refer to humans’ voices or an individual's voice features. Some spectral centroids get merely similar results due to those inclinations mentioned. This paper exposes Fuzzy Relation method to fit the need of verification procedures thorough its interval scale on any fuzzy features. The objective of verification procedure is to gain consistency measured scales, and security warrant remains valid. The inhouse experiments served to give user A of [0.49, 1.18] interval, user B of [0.76,1.07] interval, and user C of [0.44,0.95] interval, and those interval numbers are proposed to cap other login users accounts unto theirs.